The Evaluation of Child Sexual Abuse: Child Advocacy Center Example - Nurten Gülsüm Bayrak; Damla Akpınar; Fadime Üstüner Top; Sevda Uzun (Galenos Publishing House, 2022)
Objective: The purpose of the research was to evaluate the child sexual abuse cases admitted to the Child Advocacy Center (CAC) in terms of the child, family, and abuser, and to identify the associated factors. Method: The data were collected retrospectively and descriptively from the cases in the CAC using the juridical reports, family interview reports Provincial Directorate of Family and Social Policies representative reports and the data collection form developed by the researchers. Results: Within the scope of the research, 175 child victims of sexual abuse were evaluated According to this; the mean age of the abused children was in the study was 13.33+-3.33, 81.7% were girls, and 42.9% were high school students. According to the results of the study, 34.3% of the children were diagnosed with mental illness. Among the mothers and fathers included in the study, 76% of the mothers and 33.7% of the fathers are not working and also 85.1% of the mothers and 79.5% of the fathers are primary school graduates. In addition, 60% of families have a low income level. It was determined that 57.7% of the children were exposed to abuse many times and irregularly, 40.6% were exposed to sexual touching, 35.4% were exposed to penetration, and 44% medical examination. Conclusion: The study showed that family dynamics play a pivotal role in the sexual abuse of children, and low socio-economic/education level and being an adolescent girl is among the significant factors.